Feições de carste sobre a formação Serra Geral no município de São Martinho da Serra - RS - Guareschi, Vinícius Duarte (2012)
Karst features are more common in relief formed by carbonate rocks, but can occur in silica-rich rocks such as volcanic acid, a fact not yet explored. Thus, this Master's thesis aims to understand the mechanisms responsible for the development of these landforms associated volcanic rocks through the identification and mapping of karst features, analyzing its relationship with the slope, hypsometry, lithology and morpho-structural lineaments. Furthermore, we tried to relate the distribution of features with use and land cover and check the fragility of the Serra Geral Aquifer. The study area comprises the city of São Martinho da Serra - RS, basic and acidic volcanic rocks of the Serra Geral formation. For this, the karst features were identified and mapped using satellite imagery, and morpho-structural lineaments were extracted from SRTM. We generated various cartographic products, which combined with field observations, allowed to classify the karst features that occur in the study area into three types of depressions that correspond to different stages of morphological evolution: a) Depression Surface Planed Top b) Headwater drainages suspended; c) Depression in the Valley bottom. It was found that karst features are controlled by the morpho-structural lineaments, and tend to develop in portions of volcanic flows that are more easily affected by weathering. It was observed that the depressions in the surface Planed Top occur more frequently in the municipality where the land use is predominantly agricultural, denotes the fact that risk of contamination of the aquifer Serra Geral, since its recharge also occurs through these features.